O trabalhador velho na sociedade capitalista e os impactos do neoliberalismo no âmbito da previdência social - Lima, Thaysa Kelly Neves de (2017)
The present study deals with the social problems of worker aging, explaining the implications of neoliberalism in the context of Social Security and the impacts on aging workers. For that, the study was delineated having as a theoretical methodological framework the qualitative research based on the historical-dialectical perspective. In this sense, it is problematic about population aging as a heterogeneous, multifaceted and socially constituted process, highlighting the class condition as one of the fundamental determinants that directly affect the way in which old age is experienced and signified, defining the focus of research in the material conditions of the worker's existence. Such an approach has taken into account the reflexes of the capitalist logic of production that directly affect the working and working conditions of the worker, even when the latter leaves the production process in the face of old age. Based on these assumptions, the research proposed to identify how the constitution of social protection policies for the worker took place, making a social-historical construction of such policies and how they developed in the Brazilian scenario, more specifically, in the context of Social Security. Finally, we present the impacts and repercussions resulting from the political, economic and social transformations that emerged in the 1990s, based on neoliberal ideology, highlighting the implications of such changes in the scope of Social Security and the consequences for the aging worker.